Ngaben Di Krematorium Sagraha Mandra Kantha Santhi Sebagai Sebuah Solusi - Wismayani, Sang Ayu Putu (Jayapangus Press, 2023)
Bali is an island which is famous for its customs and culture that are wrapped in Hinduism. The changes that are constantly occurring lead us to the world's development that is increasingly advanced. The changes that occur refer to all aspects, including the implementation of the ngaben ceremony in Bali. Many phenomena that we find in the community, i.e. many people who carry out the funeral ceremony at the cremation place. This is caused by the fact that today's society wants everything that is practicable, economical and without reducing the meaning. This is the reason why people choose crematorium as a place to carry out the funeral process, one of which is Bebalang crematorium, Bangli. The methods used in this research are qualitative methods using literature review. Ngaben ceremony is one of the pitra Yajña ceremonies, which become the time for paying debts to ancestors. Ngaben is the ceremony of burning the corpse of Hindu in Bali. Nowadays, people are starting to turn to the crematory to carry out the process of funeral ceremonies. One of them is the Sagraha Mandra Kantha Santi Crematorium. This cremation place was recently established in 2019, but many people have carried out their funeral ceremonies in this place, especially during the pandemic. There are several reasons that causes people prefer crematoriums as a place to hold ngaben ceremonies, first, because it is very practical, it doesn't take a long time, the cost of carrying out the ceremony is also relatively cheap, and the main thing is the procession of the activities is similar to the ngaben which is carried out in traditional setras generally.